Kebutuhan Material Jaringan jalan Provinsi di Provinsi Lampung Pada Wilayah 2 dan Wilayah 4 - wahyudi, meifra; Hadi, yohanes Martono; Adha, idharmahadi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2017)
Lampung Province is a province that annually holds improvements and infrastructure development, especially in the field of roads. By the increase of the road construction, the more material needed to meet the development.This research was conducted to know the amount of material of provincial road network of Lampung province in budget year 2016 region 2 and region 4 and to get material requirement in next year.From the collection of this data, obtained the auction pattern of project implementation began in mid-year until the end of the year. And from result of calculation of material requirement of road construction project of Lampung province in 2016 got the dominant result to use Sand, Asphalt, Aggregate Coarse, and Cement. In fulfilling the material needs of the Lampung provincial road project in 2016 region 2 and region 4 is good enough, it is shown with its fulfillment of the provincial road works material in 2016. From the analysis of the calculation of provincial road material needs in 2016 can be used as a guide to face the material needs of the following year.